CHANGING SOCIAL VALUES AND MUSIC: बदलते सामाजिक मूल्य एवं संगीत - Tawse, Suvarna (International Journal of Research -GRANTHAALAYAH, 2015)
Music is a symbolic symbol of artistic achievements and musical traditions of human society. Music is considered as the social cultural heritage of society. When memories, anxiety, malice, mental tension, emotion and complex emotions make social life monotonous and rooted, then the arts especially the music arts have a special effect on the social value of society. संगीत मानव समाज की कलात्मक उपलब्धियों एवं सांगीतिक परम्पराओं का मूर्तिमान प्रतीक है।संगीत समाज की सामाजिक सांस्कृतिक विरासत मानी जाती है। जब स्मृतियाँँ,चिन्ता,द्वेष,मानसिक तनाव,आवेष तथा जटिल भावना,सामाजिक जीवन को नीरस तथा जड़ बना देती है तब कलाएँ विषेषकर संगीत कला समाज व्यक्ति के सामाजिक मूल्य पर विषेष प्रभाव डालती है।